DETERMINATION OF ANTIBODIES AGAINST TOXOPLASMA GONDII IN BUFFALOS (BUBALUS BUBALIS) OF JENARO HERRERA DISTRICT, LORETO, PERU - Esteves V., Karla (2013)
The aim of this study was to determine the seroprevalence of Toxoplasma gondii in buffalos in the Jenaro Herrera district, Loreto, Peru. A total of 70 blood samples were collected in female buffalos for the detection of antibodies against T. gondii by the Indirect Hemaglutination Test (IHA) and the Indirect Immunofluorescence Test (IFI). The results showed that 35.7 ± 11.2% of the samples were positive by IHA and 17.1 ± 8.8% were positive by IFI.